Ghandruk Old Settlements: A History of Tourism and Disaster Resilience - Yenny Rahmayati; Aljohara Alsuliman; Sama Alharti; Dimah Alharkan (Jurnal Serambi Engineering, 2023)
Located in South Asia, specifically in the southern part of the Himalayan Mountain ranges about 65 to 8.848 meters above sea level, Nepal has a wide range of cultural traditions, religions, ethnicities, and languages. The country is bordered by India on the west and China on the north. Ghandruk is one of the old historical mountain settlements in Nepal, situated on the slope of a mountain. It is also on one of the busiest tourist routes to Annapurna Base Camp and Poonhill, offering a popular tourist attraction, a hiking stopover, and a cultural representation of Gurung culture. Throughout its history, it has been subjected to numerous violent earthquakes, especially in the past century. This paper examines how the Ghandruk settlements survived as old historical settlements and from the earthquake disaster, utilizing an architectural mixedmethod research approach. The architectural typo-morphology analysis was employed as the main methodology to assess the physical changes of the settlement, supported by an ethnographic overview, particularly for socio, cultural, economic, and historical analysis. This study enriches the literature about the old historical settlements as well as can be a reference for practice, especially for tourism and disaster management purposes.